Agroextrativismo, comunidades tradicionais e os desafios na comercialização dos produtos: Januária, Norte de Minas Gerais - Yara Janaina Pinto Gusmão (2018)
This dissertation aims to analyze the commercialization of the products of agroextractivism in the community of Cabeceirinha, located in the Pandeiros river basin, in general of the left bank of the Upper São Francisco river, North of Minas Gerais, as well as to analyze the other initiatives that exist in the municipality, knowing their potentialities and difficulties. For this purpose, a qualitative field study was carried out using semi-structured interviews, which were applied to professionals from different sectors that have links with the Cabeceirinha community or the Januária agroextractivism. In addition to the questionnaires applied, a reconnaissance visit was carried out in the community studied, and on the occasion interviews were conducted with five community historians to discuss the occupation of the locality, the environmental characteristics of the region and the agroextrativism in the community . It was observed that the agroextractivism in the municipality of Januária has been growing every year, and all the initiatives showed a great productive potential; however the difficulties faced prevent the development of the activity is effective. The challenges of Cabeceirinha are similar to all agro-extractive groups: lack of animation and mobilization of groups, lack of certification of products, problems with roads and the outflow, need for a fixed consumer market and payment for products are difficulties lived in Cabeceirinha and in all agro-extractive ventures.